2018
DOI: 10.1021/acs.energyfuels.8b01223
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Benzothiophene Capture with a Metal-Modified Copper–1,3,5-Benzenetricarboxylic Acid Adsorbent

Abstract: To construct more desirable adsorption affinity between the current metal−organic frameworks and benzothiophene (BT), a novel desulfurizer (V/Cu−BTC, where BTC represents 1,3,5-benzenetricarboxylic acid) was prepared by reducing Cu(II) to Cu(I) with V(III) on Cu−BTC using a hydrothermal synthesis method. Using nitrogen adsorption− desorption, powder X-ray diffraction, scanning electron microscopy, Fourier transform infrared spectroscopy, and X-ray photoelectron spectroscopy, we approved that the modifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 37 publications
(83 reference statements)
0
65
0
Order By: Relevance
“…Among the various types of MOFs, copper benzene tricarboxylate Cu-BTC or Cu 2 (BTC) 3 (also called HKUST-1 or MOF-199) [21] [22] is one of the distinguished structure together with the IRMOF series. Cu-BTC was rst reported in 1999 by Chui et al [23] and has attracted considerable attention both theoretically and experimentally [24].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various types of MOFs, copper benzene tricarboxylate Cu-BTC or Cu 2 (BTC) 3 (also called HKUST-1 or MOF-199) [21] [22] is one of the distinguished structure together with the IRMOF series. Cu-BTC was rst reported in 1999 by Chui et al [23] and has attracted considerable attention both theoretically and experimentally [24].…”
Section: Introductionmentioning
confidence: 99%
“…So far, a bunch of adsorbents have been reported for desulfurization, such as metal oxides, 13 active carbon, 14 zeolites, [15][16][17] mesoporous materials 18,19 and metal-organic framework (MOF) materials. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Among them, MOFs are getting more and more interest in adsorption desulfurization in recent years because of the high specic surface areas, highly ordered threedimensional pore structures, and easy modication of pore size and shape. 20 Based on these advantages, some pristine MOFs have been investigated in adsorption desulfurization.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Besides these, some MOFs built by the same ligand but different metal ions have also been studied to investigate the effect of central metals on the desulfurization performance, since the coordinated unsaturated central metals are considered as the adsorption sites for desulfurization. [26][27][28][29][30][31][32][33] Khan et al 26 studied the removal of BT using three analogous MOFs MIL-53(Al, Cr, V) and found that MIL-47(V) showed the best adsorption capacity. This result was ascribed to the highest acidity of MIL-47(V), though the origin of acidity was not clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we propose an oCNTs/ILs catalytic system for the oxidation of dibenzothiophene (DBT) with H 2 O 2 as the oxidant. The oxidation of aromatic thiophene is one of the most important reactions to remove the aromatic sulfur-containing compounds from the fuel [37,38] . oCNTs were chosen as model carbon catalysts to probe the influence of different oxygen groups and ILs on the catalytic system.…”
Section: Introductionmentioning
confidence: 99%